Ratio legis kewajiban untuk menjaga dan menghormati norma agama berdasarkan Undang-Undang Kepariwisataan - Dwi Aryanti Ramadhani; Aji Lukman Ibrahim; Rianda Dirkareshza (Jurnal Cakrawala Hukum, 2021)
Pandeglang Regency is a tsunami-affected area in the Sunda Strait. In order to rebuild tourism, it is necessary to formulate an integrated planning by compiling regulations on tourism. This study aims to determine the Ratio Legis obligation to maintain and respect religious norms for tourists in tourism laws and to find out the form of legal protection for tourists who violate religious norms in tourist attractions. The research method used is in the form of normative legal research complemented by interviews with the head of the tourism village in Pandeglang district. The results showed that the ratio legis obligation to maintain and respect religious norms, customs, culture, and values that live in the community for tourists so that the local culture is not contaminated with foreign cultures brought by tourists. Then the sanctions applied only in the form of a warning are not commensurate with the losses incurred.How to cite item: Ramadhani, D., Ibrahim, A., Dirkareshza, R. (2021). Ratio legis kewajiban untuk menjaga dan menghormati norma agama berdasarkan Undang-Undang Kepariwisataan. Jurnal Cakrawala Hukum, 12(2), 159-167. doi:https://doi.org/10.26905/idjch.v12i2.5353